The Quality of Bio-pellets Made by Combining Walnut Kernel Shells (Canarium Indicum L.) from Bogor, Indonesia, and Palm Kernel Shells as Renewable Energy - Iryani, Ani; Kusumawardani, Linda Jati; Juniansyah, Ronaldo (UI Scholars Hub, 2025)
Using biomass as an energy source helps overcome the declining supply of fossil fuels. Bio-pellets—an energy product made from biomass—is one option that can be utilized. One source of biomass energy is walnut kernel shells. The walnut plant (Canarium indicum L.) is a forest tree grown in eastern Indonesia. The walnut plant is also located in the GOR Pajajaran area of Bogor City and has not been utilized for energy production. This study consists of three stages: 1) raw material preparation, 2) bio-pellet production, and 3) bio-pellet characterization in accordance with the Indonesian National Standard (SNI) 8951:2020. Based on the results of our study, bio-pellets made from 100% walnut kernel shells can be utilized as fuel, with a calorific value of 4,593 cal/g. Although the moisture content remains high, the calorific value still meets the standard for power plants according to SNI 8951:2020. In addition, palm kernel shells can improve the quality of bio-pellet products. The combination of 30% walnut kernel shells and 70% palm kernel shells improves calorific value, with the following specifications: 4,684.4 cal/g of calorific value, 8.83% moisture content, 1.85% ash content, 69.16% volatile materials, 19.30% fixed carbon, 0.02% sulfur content, and 1.18% bulk density.